Infective endocarditis due to Streptococcus agalactiae in the puerperal period. Issue 6 (23rd March 2021) - Nakamura, Takeshi; Seo, Kohei; Okuyama, Ayumi; Ichizuka, Kiyotake; Sekizawa, Akihiko; Nagatsuka, Masaaki
Abstract: Streptococcus agalactiae, also known as group B Streptococcus, is a species of bacteria occasionally detected in the vagina and/or rectum of pregnant women. This report describes the case of a 33‐year‐old woman who developed infective endocarditis on puerperal day 17, owing to group B Streptococcus, and required lifesaving surgery. The patient was rushed to our hospital with chief complaints of fever and fatigue. After hospitalization, antibiotics were administered; however, the symptoms did not improve. Following a detailed examination, vegetation was found in the heart, suggestive of infective endocarditis. Surgical removal of the vegetation improved the patient's condition. The development of group B Streptococcus infection and infective endocarditis in a pregnant woman with no risk factors is rare. This case confirms that this patient's life was saved by a timely diagnosis and appropriate therapeutic intervention.